Assessment of KRASG12C inhibitors for colorectal cancer - Piazza, Gary A.; Chandrasekaran, Preethi; Maxuitenko, Yulia Y.; Budhwani, Karim I. (Frontiers in Oncology, 2024)
Colorectal cancer (CRC) is a highly prevalent and lethal cancer worldwide. Approximately 45% of CRC patients harbor a gain-in-function mutation in KRAS. KRAS is the most frequently mutated oncogene accounting for approximately 25% of all human cancers. Gene mutations in KRAS cause constitutive activation of the KRAS protein and MAPK/AKT signaling, resulting in unregulated proliferation and survival of cancer cells and other aspects of malignant transformation, progression, and metastasis. While KRAS has long been considered undruggable, the FDA recently approved two direct acting KRAS inhibitors, Sotorasib and Adagrasib, that covalently bind and inactivate KRAS G12C . Both drugs showed efficacy for patients with non-small cell lung cancer (NSCLC) diagnosed with a KRAS G12C mutation, but for reasons not well understood, were considerably less efficacious for CRC patients diagnosed with the same mutation. Thus, it is imperative to understand the basis for resistance to KRAS G12C inhibitors, which will likely be the same limitations for other mutant specific KRAS inhibitors in development. This review provides an update on clinical trials involving CRC patients treated with KRAS G12C inhibitors as a monotherapy or combined with other drugs. Mechanisms that contribute to resistance to KRAS G12C inhibitors and the development of novel RAS inhibitors with potential to escape such mechanisms of resistance are also discussed.